Prevalence of Overconsumption of Salt and its Determinants – The Case of Southwestern Rural China - Tony, Ka chun YUNG; Rainbow, Hiu yan MOK (International Journal of Nutrition, 2020)
Aim Overconsumption of salt contributes to hypertension and increases the risks of cardiovascular diseases. Most studies that investigated salt intake by applying the Health belief model (HBM) have focused on urban settings. This study aims to identify the prevalence of salt overconsumption (>6 g per day) in a rural village in Southwestern China and to determine the association between knowledge regarding salt consumption/HBM constructs and salt overconsumption behavior among village residents. Methods Inthis cross-sectional study, 79 adults aged 18 years and above were interviewed using household-based and face-to-face questionnaires. Salt intake was measured using an electronic balance in accordance with a previous protocol. Results Our finding showed that the average daily salt intake is 11.19±11.14 (mean±SD) g. Moreover, 64.6% of the participants overconsumed salt. None of the participants was aware of the national recommendation for salt intake. Univariate logistic regression showed that i) knowledge about hypertension causing cardiovascular diseases (odds ratio [ORu]=3.02), ii) perceived severity of hypertension as a serious disease (ORu=4.92), and iii) perceived benefit of reducing salt intake to prevent hypertension (ORu=3.52) were unexpectedly positively associated with salt overconsumption behavior. All the studied sociodemographic factors were not associated with salt overconsumption behavior. Conclusions A high prevalence of salt overconsumption was found among residents of rural villages in Southwestern China. HBM was unable to explain the causal relationship between its constructs and salt overconsumption behavior. The extremely low awareness of the national salt recommendation highlighted the urgent need to provide relevant health education in rural China.
Keywords: salt overconsumption; rural settings; Southwestern China